The Issue of Disadvantaged Situation and Pandemic - Perge, Anna; Somosi, Mariann Veresné (European Journal of Social Science Education and Research, 2023)
In the examination of the effects of the COVID-19 pandemic, special attention should be paid to the lagging areas. In the case of the settlements where we should reckon with social and economic backwardness and/or unemployment exceeding the national average, even the smallest change can move the life chances of people living there to a significantly negative direction. We would like to support the theory that the pandemic has resulted in further adverse consequences in disadvantaged settlements besides the existing economic and life quality disadvantages by research performed in Hungary. Besides the infrastructural deficiencies of the families’ homes, it is also important to examine the infrastructural elements in terms of the settlements and health care, since health care, including human resources, is a cardinal issue in connection with the efforts to curb the pandemic. Besides these, we should reckon with the changes in the level of unemployment, the possible long-lasting incapacity for work. In the light of the research, it can be defined which professionals’ presence and competencies are essential in disadvantaged settlements to prevent the further growth of disadvantages.